Integrative metabolomic and transcriptomic analysis reveals difference in glucose and lipid metabolism in the longissimus muscle of Luchuan and Duroc pigs - Deng, Liyan; Li, Wangchang; Liu, Weiwei; Liu, Yanwen; Xie, Bingkun; Groenen, Martien A. M.; Madsen, Ole; Yang, Xiaogan; Tang, Zhonglin (Frontiers in Genetics, 2023)
In this study, the metabolic and transcriptomic profiles of longissimus dorsi muscle from Duroc and Luchuan pigs were compared. A total of 609 metabolites were identified, 77 of which were significantly decreased in Luchuan compared to Duroc, and 71 of which were significantly elevated. Most differentially accumulated metabolites (DAMs) upregulated in Luchuan were glycerophospholipids, fatty acids, oxidized lipids, alcohols, and amines, while metabolites downregulated in Luchuan were mostly amino acids, organic acids and nucleic acids, bile acids and hormones. From our RNA-sequencing (RNA-seq) data we identified a total of 3638 differentially expressed genes (DEGs), 1802 up-regulated and 1836 down-regulated in Luchuan skeletal muscle compared to Duroc. Combined multivariate and pathway enrichment analyses of metabolome and transcriptome results revealed that many of the DEGs and DAMs are associated with critical energy metabolic pathways, especially those related to glucose and lipid metabolism. We examined the expression of important DEGs in two pathways, AMP-activated protein kinase (AMPK) signaling pathway and fructose and mannose metabolism, using Real-Time Quantitative Reverse Transcription PCR (qRT-PCR). Genes related to glucose uptake, glycolysis, glycogen synthesis, fatty acid synthesis (PFKFB1, PFKFB4, MPI, TPI1, GYS1, SLC2A4, FASN, IRS1, ULK1) are more activated in Luchuan, while genes related to fatty acid oxidation, cholesterol synthesis (CPT1A, HMGCR, FOXO3) are more suppressed. Energy utilization can be a decisive factor to the distinctive metabolic, physiological and nutritional characteristics in skeletal muscle of the two breeds we studied. Our research may facilitate future porcine breeding projects and can be used to reveal the potential molecular basis of differences in complex traits between various breeds.